An Analysis of Relation Among Three Levels of Ala–Tragus Line and Natural Occlusal Plane in Young Dentulous Subjects – A Cross-sectional Photographic Study - Khyati N. Gosai; Ina B. Patel; Pooja Poonia; Dhvani P. Jadav; Nirali D Patel; Prakruti H Sanghani (Journal of Pharmacy and Bioallied Sciences)
Occlusal plane determination plays an evident role in successful rehabilitation of completely edentulous patients. The most commonly used method is by using Camper’s plane. But the posterior reference point of Camper’s plane is debatable according to available literature. The aim of this study was to determine the most reliable posterior reference point for Camper’s plane. A cross-sectional study was conducted, in which 60 dentulous subjects with age ranging from 18 to 25 years were selected according to the inclusion criteria. The Fox plane was inserted and lateral photographs were taken. A screen protractor was used to measure the angle between the occlusal plane and three ala–tragus lines. All three ala–tragus lines had the inferior border of ala of the nose as the anterior point of reference and for posterior reference, they used superior, middle, or inferior point of the tragus. The ala–tragus line using the inferior point of the tragus had the least mean angle with the occlusal plane. One-way analysis of variance (ANOVA) test obtained a P-value of < 0.0001, and therefore, a statistically significant difference was present among all three lines. Also, post hoc Tukey’s honestly significant difference test for intergroup comparison of difference in angle among three different lines with the occlusal plane showed a significant P-value on comparing all three groups between each other. The ala–tragus line formed using the inferior point of the tragus was most parallel to the occlusal plane in dentate patients. Therefore, the inferior point of the tragus should be used for Camper’s plane.